A Review of Applications of Speech Synthesis Technology - Xiong, Wenhao (Transactions on Computer Science and Intelligent Systems Research, 2025)
Currently, the development of visual technologies and applications is much more advanced than that of speech, but as both speech and vision are equally important and attractive, their potentials should be comparable. In order to develop speech technology and prove its application potential, this paper presents current status of speech synthesis technology in four applications: spoken language education, digital music, virtual character, and language protection and dissemination, and then points out its potential in different stages of spoken language learning, music generation similar to current picture generation, virtual characters that move people in ways other than through singing, and new ways of voice protection and dissemination both directly and indirectly, and finally discusses the balance of the development of speech synthesis technology. By analyzing several potential applications of speech synthesis technology from application areas, this paper not only proves the development potential of speech, but also shows the way for subsequent research to find innovative inspiration from application areas.